Dnmt1 has an essential function despite the absence of CpG DNA methylation in the red flour beetle Tribolium castaneum. Issue 1 (December 2018) - Schulz, Nora; Wagner, C.; Ebeling, Julia; Raddatz, Günter; Diddens-de Buhr, Maike; Lyko, Frank; Kurtz, Joachim
Abstract Epigenetic mechanisms, such as CpG DNA methylation enable phenotypic plasticity and rapid adaptation to changing environments. CpG DNA methylation is established by DNA methyltransferases (DNMTs), which are well conserved across vertebrates and invertebrates. There are insects with functional DNA methylation despite lacking a complete set ofDnmts . But at least one of the enzymes, DNMT1, appears to be required to maintain an active DNA methylation system. The red flour beetle, Tribolium castaneum, lacksDnmt3 but possessesDnmt1 and it has been controversial whether it has a functional DNA methylation system. Using whole genome bisulfite sequencing, we did not find any defined patterns of CpG DNA methylation in embryos. Nevertheless, we foundDnmt1 expressed throughout the entire life cycle of the beetle, with mRNA transcripts significantly more abundant in eggs and ovaries. A maternal knockdown ofDnmt1 caused a developmental arrest in offspring embryos. We show thatDnmt1 plays an essential role inT. castaneum embryos and that its downregulation leads to an early developmental arrest. This function appears to be unrelated to DNA methylation, since we did not find any evidence for this modification. This strongly suggests an alternative role of this protein.